APUCEN PRESIDENT’S INAUGURATION CEREMONY – COMMUNITY ENGAGEMENT THROUGH KNOWLEDGE EXCHANGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
BRUNEI DARUSSALAM, 5 December 2016 In the direction to promote universitycommunity engagement, the AsiaPacific UniversityCommunity Engagement Network (APUCEN)’s new President, Professor Datuk Dr. Asma Ismail, in her new Presidency speech, promised to strive to work together hand in hand with all members of APUCEN to move to higher levels in UniversityCommunity Engagement.